The Significance of Ayurvedic Medicinal Plants - Syal Kumar MD; Gustav J. Dobos MD; Thomas Rampp MD (SAGE Publishing, 2017)
Traditional Indian medicine (ayurveda) is becoming increasingly popular, with many chronic conditions responding to it well. Most patients begin to take conventional medications as soon as their diagnoses are made, so ayurvedic treatments are usually undergone alongside and/or after conventional medical approaches. A detailed knowledge of the action of food, spices, and medicinal plants is needed in order to understand their potential influence fully. While societal use of ayurvedic plants and Indian spices is commonplace, without ill effect, the use of more concentrated products made from single plants, often in the form of teas or tablets, is of more concern. The mechanisms by which polyherbal drugs and their extracts act differ in many respects from the actions of single substances or synthetic drugs. Despite the fact that ayurvedic medicines are based on natural herbal materials, their safety depends on their method of administration, taking into account individuals' needs and their specific disease conditions.